Smart City Implementation in Urban Infrastructure Management - Mohamad Djaelani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The idea of "smart cities" has drawn more and more attention worldwide as a way to solve the problems that big cities face, particularly in managing urban infrastructure. By utilizing information and communication technology, The goal of a smart city is to give its citizens a more sustainable, livable, and efficient environment. The purpose of this essay is to examine how smart city principles are applied to urban infrastructure management, focusing on the use of intelligent technologies in transportation, energy, water, and waste management. According to research findings based on a review of the literature and actual data, smart city projects can increase the sustainability and efficiency of municipal infrastructure while also improving the quality of life for urban dwellers.